VASCULAR WALL STIFFNESS IN PATIENTS WITH ANKYLOSING SPONDYLITIS: RESULTS OF A MULTICENTER STUDY - I. Z. Gaydukova; A. L. Maslyansky; O. L. Polyanskaya; E. P. Kolesova; A. P. Rebrov; A. O. Konradi (Klinicist)
Objective: to study some vascular wall stiffness parameters in patients with ankylosing spondylitis (AS) without clinically manifest cardio vascular diseases. Subjects and methods. One hundred and six patients with AS and 21 healthy volunteers without cardiovascular diseases who were matched for age, gender, and cardiovascular risk were examined at two centers. Cardiovascular risk and vascular wall stiffness (augmentation index and pulse wave propagation velocity (PWPV)) were assessed by oscillography. Results. Vascular wall stiffness was comparable in the patients with AS (at both centers) and in the healthy individuals. PWPV was 7.45 (5.4–8.71) m/sec in the AS patients (n = 106) and 8.53 (6.28–9.5) m/sec in the healthy individuals (n = 21); the aortic augmentation in dex was 15.6 (7.9–31.1) and 21.1 (10.2–24) %, respectively; p > 0.05 for all. Correlation analysis revealed associations between aug mentation index, age, blood pressure, disease activity (BASDAI) and spine mobility (BASMI) scores. Conclusion. The vascular wall stiffness did not differ between AS patients without cardiovascular diseases and cardiovascular riskmatched healthy individuals. Its parameters were related to age, blood pressure, and disease activity (BASDAI) and axial skeleton immobility (BASMI) indices.